Suspended from Work and School? Impacts of Layoff Events and Unemployment Insurance on Student Disciplinary Incidence - Riley Acton; Jo Al Khafaji-King; Austin C. Smith (Institute of Labor Economics (IZA), 2023)
We examine the impact of local labor market shocks and state unemployment insurance (UI) policies on student discipline in U.S. public schools. Analyzing school-level discipline data and firm-level layoffs in 23 states, we find that layoffs have little effect on discipline rates overall. However, effects differ across the UI benefit distribution. At the lowest benefit level (265/week), a mass layoff increases out-of-school suspensions by 4.5%, with effects dissipating as UI benefits increase. Effects are consistently largest for Black students - especially in predominantly White schools - resulting in increased racial disproportionality in school discipline following layoffs in low-UI states.
Keywords: I24; J63; J65; 330; school discipline; layoffs; unemployment insurance